Characteristics of upright versus supine reflux pattern in patients with laryngopharyngeal reflux - Tamer A. Mesallam; Abdulsalam A. Baqays (Brazilian Journal of Otorhinolaryngology, 2021)
Introduction: Many laryngeal-related problems have been attributed to laryngopharyngeal reflux including dysphonia, frequent throat clearing, chronic cough, and globus sensation. However, there is still controversy regarding diagnosis and clinical presentation of this disorder. Objective: The main objective of this study is to describe laryngopharyngeal reflux characteristics of different reflux position patterns in laryngopharyngeal reflux patients diagnosed with oropharyngeal pH monitoring. Methods: A retrospective chart review was conducted for 161 laryngopharyngeal reflux patients diagnosed with 24 h oro-pharyngeal pH monitoring. Study subjects were categorized into upright and supine laryngopharyngeal reflux groups based on the pH results. The two groups were compared regarding the clinical presentation and pH characteristics. Results: Significant higher rates of upright laryngopharyngeal reflux position than supine laryngopharyngeal reflux position (P < 0.0001) were reported among the study group. Reflux symptoms index results were significantly higher in the upright larybgopharyngeal reflux group compared to the supine laryngopharyngeal reflux group. 24 h oropharyngeal pH measurements composite Ryan score was significantly higher in the upright group compared to the supine group (P < 0.0001). No significant difference was found between the upright and supine laryngopharyngeal reflux groups regarding the frequency of clinical presentation or voice handicap index ratings. Conclusion: Laryngopharyngeal reflux was found to be more prevalent occurring in the upright position among the study group. Reflux-related characteristics including pH parameters were more evident in the upright laryngopharyngeal reflux position.